Studies on cryptosporidiosis: Advances in immune-based control strategies and parasite cryopreservation. - Jaskiewicz, Justyna. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Saul Tzipori.; Committee: Charles Shoemaker, Giovanni Widmer, and Shannon Tennant.; Keywords: Parasitology, Immunology, and Veterinary science.